Modulation of FOXP3 Gene Expression in OVCAR3 Cells Following Rosmarinic Acid and Doxorubicin Exposure - Veysel Toprak; İlhan Özdemir; Şamil Öztürk; Orhan Yanar; Yusuf Ziya Kizildemir; Mehmet Cudi Tuncer (Pharmaceuticals)
Background/Objectives: Ovarian cancer has the highest mortality rate in the world. Treatment methods are listed as surgery, chemotherapy, and radiotherapy, depending on the stage of cancer, but developing resistance to chemotherapy increases the need for alternative agents that act on the same pathways. The effects of rosmarinic acid (RA) and doxorubicin (DX) on the activation of FOXP3, an important tumor suppressor gene, in OVCAR3 cells were examined. Materials and Methods: In this study, a human ovarian adenocarcinoma cell line was used. MTT analysis was performed to reveal the result of RA and DX on ovarian cancer cell proliferation. Expression levels of FOXP3 for cell proliferation and Capase-3 for apoptosis were determined by RT-qPCR. The wound healing model was applied to determine cell migration rates. The results were evaluated with one-way ANOVA in an SPSS 20.0 program as p ≤ 0.05. Results: It was determined that RA and DX alone and in combination inhibited the proliferation of OVCAR3 cells in different doses for 24, 48, and 72 h, and caused the cells to die by causing them to undergo apoptosis. Caspase-3 expression increased approximately tenfold in OVCAR3 cells, while FOXP3 expression was upregulated only in RA treatment and was downregulated in DX and RA + DX treatments. Conclusions: According to the results of our study, it was determined that the FOXP3 signaling pathway related to apoptosis, and proliferation was affected by the combination treatment of RA and DX in the OVCAR3 cancer cell line. This shows that RA will gain an important place in cancer treatment with more comprehensive study.